IMPLEMENTATION ANALYSIS OF ARTICLE 102 ITEM 2 OF LAW NUMBER 13 OF 2003 REGARDING MANPOWER (STUDY ON THE FEDERATION OF INDONESIAN PULP AND PAPER WORK UNIONS) - Indah Satria; Gilang Prayoga; Aulia Oktarizka Vivi Puspita Sari A.P; Sanyyah Majidah (Constitutional Law Society, 2022)
Dozens of workers at Tanjung Enim Lestari Limited Liability Company experienced unilateral termination of employment. This happens because of the contract work system and the change of vendors providing worker services, the paper raw material producing company that was founded in 1990, often changes to the vendor supplier of labor. However, neither the Tanjung Enim Lestari Company nor the labor provider vendors encountered the mass of labor unions who held a demonstration. The author uses two problem approaches, namely the normative juridical approach and the empirical approach. The finding in this article is that workers' welfare rights are not fulfilled during/after the work period, in Article 99 of Law Number 24 of 2011 concerning the Social Security Administering Body, it is stated that every worker or laborer and his family have the right to obtain labor social security. that the employer is obliged to gradually register himself and his workers as participants with the Social Security Administering Body and the company is also obliged to provide welfare facilities and form worker or labor cooperatives and productive businesses.